Lightweight high-strength geopolymer concrete suitable for fabricated building and preparation method thereof

The polymer of solid waste generation is stimulated by alkali exciter, and combined with fibers and composite admixtures, the problem of lightweight concrete being difficult to take into account both lightweight and high strength is solved, and the preparation of lightweight high-strength concrete is achieved efficient and environmentally friendly, suitable for the preparation of lightweight high-strength concrete. Prefabricated building.

CN119461985AActive Publication Date: 2025-02-18GUANGZHOU METRO DESIGN & RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411693249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

It is difficult for existing lightweight concrete to take into account both lightweight and high strength while ensuring low energy consumption and low pollution. In addition, traditional cement has problems of high energy consumption and high pollution in the production process.

Method used

The alkali triggers stimulate the potential activity of solid waste such as waste ceramic powder, fly ash and slag, and generates polymers to replace traditional ordinary cement as a binder, and combines mixed fibers and composite admixtures to enhance light bones The strength and properties of material concrete.

Benefits of technology

It has achieved high strength of lightweight concrete. The raw materials used are solid waste, with low cost and simple process, and meets the requirements of environmental protection and sustainable development. It is suitable for prefabricated buildings such as bridges, high-rise buildings, tunnel pipes, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151515030000091
    Figure BDA0005151515030000091
  • Figure BDA0005151515030000101
    Figure BDA0005151515030000101
Patent Text Reader

Abstract

The invention provides lightweight high-strength geopolymer concrete suitable for prefabricated buildings. The lightweight high-strength geopolymer concrete is prepared from the following components in parts by weight: 90 to 180 parts of waste ceramic powder, 45 to 135 parts of fly ash, 225 to 315 parts of slag, 158 to 256 parts of alkali activator, 626 to 765 parts of fine aggregate, 504 to 576 parts of light coarse aggregate, 4.5 to 13.5 parts of mixed fiber and 1 to 36 parts of composite additive solution. The light and high-strength shale ceramsite is used as the light coarse aggregate, so that the dead weight of the concrete is reduced; potential activity of solid waste such as waste ceramic powder, fly ash and slag is excited through an alkali activator, a geopolymer is generated, the strength of the lightweight aggregate concrete is improved, and the characteristic of light weight is kept; by adding the mixed fiber and the composite admixture, the performance of the lightweight aggregate concrete is further improved. Therefore, light weight and high strength are taken into account, and the composite material can be applied to various fabricated buildings such as bridges, high-rise buildings, tunnel segments and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lightweight concrete, and in particular relates to a lightweight and high-strength geopolymer concrete suitable for assembled buildings and a preparation method thereof. Background Art

[0002] Prefabricated buildings have gradually become a hot spot in the construction industry due to their advantages such as fast construction speed, stable quality, energy saving and environmental protection. However, during the construction process, prefabricated buildings face the problem of difficult transportation and lifting of components. Lightweight concrete, as a concrete material with light weight and high specific strength, has been widely used in projects such as roads, large-span bridges, high-rise buildings, and tunnel segments. The density of ordinary concrete is about 2350kg / m 3 , while the density of lightweight concrete usually does not exceed 1950kg / m 3 , which can effectively reduce the dead weight of prefabricated building components, thereby reducing the difficulty during transportation and lifting.

[0003] There are two main design ideas for existing lightweight concrete: one is to form a porous structure by introducing gas or foam; the other is to use lightweight aggregate to partially or completely replace traditional aggregates. The latter has higher strength and is more suitable for structural applications. For example, the Chinese patent document with publication number CN115974482A discloses a lightweight and highly durable concrete and its preparation method. The material not only improves the strength but also inhibits the expansion of cracks by adding basalt fiber and polyacrylonitrile fiber. The 28-day compressive strength can reach up to 42.6MPa. However, although this concrete is lightweight, its strength cannot fully meet the needs of prefabricated buildings such as bridges, high-rise buildings, and tunnel segments. Moreover, the cement used in this technology has problems such as high energy consumption and high pollution in the production process, which does not meet the requirements of contemporary sustainable development.

[0004] Geopolymer is a hydraulic cementitious material generated by the reaction of amorphous aluminum silicate materials and alkaline activators. In recent years, geopolymer has gradually attracted attention due to its fast coagulation, high strength, good durability, low energy consumption, low pollution and ability to treat solid waste, and is considered to be one of the effective substitutes for traditional cement. The Chinese patent document with publication number CN113264719A discloses a geopolymer-based foamed concrete for roads and a preparation method thereof. The material has the advantages of light weight, heat resistance, good stability, good fluidity, and a strength far higher than the 0.6MPa required by the specification. However, this material reduces weight by introducing foam, and its strength is difficult to compare with concrete reduced by using lightweight aggregates, and is not suitable for structural applications, which limits the scope of application of geopolymers to a certain extent.

[0005] In summary, under the premise of ensuring low energy consumption and low pollution, how to expand the application scope of geopolymers, use them in conjunction with lightweight aggregates in the field of lightweight concrete, and at the same time solve the technical problem that existing concrete cannot take into account both lightness and strength, has gradually become a research hotspot in this field. Summary of the invention

[0006] In response to the above technical difficulties, the present invention provides a lightweight and high-strength geopolymer concrete suitable for prefabricated buildings, which achieves both lightweight and high strength of concrete. Moreover, the raw materials used in the present invention are all solid waste, with low cost and simple preparation process, which meets the requirements of environmental protection and sustainable development. The final product can be used in prefabricated buildings such as bridges, high-rise buildings, and tunnel segments.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A lightweight high-strength geopolymer concrete suitable for prefabricated buildings, comprising the following components and their weight proportions: 90-180 parts of waste ceramic powder, 45-135 parts of fly ash, 225-315 parts of slag, 158-256 parts of alkali activator, 626-765 parts of fine aggregate, 504-576 parts of light coarse aggregate, 4.5-13.5 parts of mixed fiber; 1-36 parts of composite admixture solution; the alkali activator is a 1-2M sodium silicate solution;

[0009] The mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:1.5 to 3;

[0010] The composite admixture solution is prepared from an organic water reducer, an inorganic retarder and water in a mass ratio of 1 to 3:1:6 to 12;

[0011] The total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag.

[0012] The present invention uses an alkali activator to activate the potential activity of solid wastes such as waste ceramic powder, fly ash and slag to generate geopolymers to replace traditional ordinary cement as a binder, thereby improving the strength of lightweight aggregate concrete and maintaining its lightweight characteristics. The performance of lightweight aggregate concrete is further improved by adding mixed fibers and composite admixtures.

[0013] The composite admixture solution of the present invention is composed of two or more additives and water, wherein the organic water reducer is used to improve dispersibility and enhance fluidity; the inorganic retarder is used to delay the formation time of the gel to prevent the coagulation time from being too fast for subsequent operations; and the total water content in the alkali activator and the composite admixture solution is limited, which ensures fluidity without being too dilute to affect the strength after hardening.

[0014] Preferably, the lightweight high-strength geopolymer concrete comprises the following components and their weight proportions: 90 parts of waste ceramic powder, 45 parts of fly ash, 315 parts of slag, 207 parts of alkali activator, 695 parts of fine aggregate, 540 parts of light coarse aggregate, 9 parts of mixed fiber; 18 parts of composite admixture solution; the alkali activator is a 1.5M sodium silicate solution;

[0015] The mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3;

[0016] The composite admixture solution is prepared from an organic water reducer, an inorganic retarder and water in a mass ratio of 1:1:6;

[0017] The total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag.

[0018] Preferably, the waste ceramic powder is prepared by crushing, washing, selecting and ball milling ceramic waste such as wall tiles, floor tiles, and daily ceramics, and the particle size is 325-800 meshes.

[0019] Preferably, the fly ash is of grade I or II, and the total content of SiO2 and Al2O3 is not less than 80wt%; and the slag is S95 grade blast furnace granulated slag powder.

[0020] The waste ceramic powder in the present invention is a powder made by crushing, washing, selecting and grinding ceramic waste such as wall tiles, floor tiles, daily ceramics, etc. with a ball mill, and its main components are silicon dioxide and aluminum oxide; fly ash is a fine powder collected from flue gas by a dust removal device in the process of burning coal to generate electricity in a power plant, and is mainly composed of minerals and unburned carbon; the effective components such as SiO2 and Al2O3 in grade I or II fly ash are higher, and the fineness requirement is also higher; slag is a molten product with silicate and aluminosilicate as main components generated by the reaction of remaining impurities such as silicon dioxide and aluminum oxide with lime after extracting metal from iron ore in the metal smelting process, and the slag is formed after quenching and granulation; the present invention applies ceramic waste and industrial waste generated in the daily production process of the steel, electric power and other industries to the preparation of lightweight concrete required for prefabricated buildings, realizes the recycling of waste, reduces the preparation cost of concrete, and meets the requirements of environmental protection and sustainable development.

[0021] Preferably, the preparation process of the alkali activator is as follows: 2.3-3.4M industrial water glass is used as a raw material, and sodium hydroxide and water are added in proportion to adjust the modulus M.

[0022] The so-called modulus refers to the molar ratio of SiO2 and Na2O in the sodium silicate solution. Adding sodium hydroxide (NaOH) can increase the ratio of Na2O in the solution, thereby reducing the modulus, while water plays a diluting role. Industrial water glass with a modulus of 2.3 to 3.4 is relatively easy to obtain. In the actual preparation process, it can also be prepared from sodium silicate solutions of other moduli. The preparation process belongs to conventional technical means known to those skilled in the art.

[0023] Preferably, the fine aggregate is medium sand; the light coarse aggregate is shale ceramsite with a particle size of 5 to 20 mm and a bulk density of 700 to 900 kg / m 3 .

[0024] The present invention selects shale ceramsite (also known as expanded shale) as light coarse aggregate. Shale ceramsite is a lightweight porous artificial aggregate made from high-quality shale by high-temperature roasting. It can replace traditional crushed stone coarse aggregate and significantly reduce the deadweight of concrete.

[0025] Preferably, in the mixed fibers, the polyvinyl alcohol fibers have a length of 2 to 4 mm and a diameter of 14 to 16 μm; and the basalt fibers have a length of 5 to 7 mm and a diameter of 16 to 18 μm.

[0026] The mixed fiber in the present invention is a mixture of polyvinyl alcohol fiber and basalt fiber, wherein the polyvinyl alcohol fiber is used to inhibit micro cracks; the basalt fiber is used to control the expansion of macro cracks; the two fibers work synergistically to form a crack control system from micro to macro.

[0027] Preferably, in the composite admixture solution, the organic water reducer is a polycarboxylic acid water reducer; and the inorganic retarder is zinc sulfate.

[0028] The organic water reducer and inorganic retarder in the present invention must be suitable for geopolymer systems, such as polycarboxylic acid water reducer and zinc sulfate. Polycarboxylic acid water reducer is a new type of green and environmentally friendly organic water reducer suitable for geopolymer systems, which has the advantages of high water reduction rate, small slump loss, high dispersibility, etc. Even at a low content, it can make the slurry have higher fluidity; zinc sulfate can make the geopolymer slurry maintain plasticity for a long time, thereby adjusting the setting time of the slurry. In addition to zinc sulfate, the inorganic retarder can also be barium chloride, borax, etc.

[0029] The present invention also provides a method for preparing the lightweight and high-strength geopolymer concrete, comprising the following steps:

[0030] S1, mixing water glass, sodium hydroxide and water in proportion to prepare an alkali activator of the required modulus for standby use;

[0031] S2. Soak the light coarse aggregate in water for 1 to 2 hours, and then spread it out to dry naturally until it reaches a saturated surface dry state, thereby obtaining pre-soaked light coarse aggregate;

[0032] S3, diluting and mixing the organic water reducing agent, the inorganic retarder and water in proportion to obtain a composite admixture solution;

[0033] S4, weighing the waste ceramic powder, fly ash, slag and fine aggregate by weight, stirring them evenly, and then adding them to the pre-soaked light coarse aggregate obtained in step S2, stirring them evenly again, to obtain a mixed system I;

[0034] S5. Add the alkali activator obtained in step S1 and the composite admixture solution obtained in step S3 to the mixed system I obtained in step S4 in sequence, stir evenly, add the mixed fiber thereto, and continue stirring so that the slurry fully wraps the fine aggregate, light coarse aggregate and fiber.

[0035] Preferably, the uniform stirring in step S4 is stirring at a speed of 30 to 60 rpm for 1 to 3 min; the uniform stirring again is stirring at a speed of 30 to 60 rpm for 1 to 3 min; the uniform stirring in step S5 is stirring at a speed of 30 to 60 rpm for 1 to 3 min; the continued stirring is stirring at a speed of 30 to 60 rpm for 1 to 3 min.

[0036] The present invention uses lightweight and high-strength shale ceramsite as light coarse aggregate to replace traditional crushed stone coarse aggregate, significantly reducing the deadweight of concrete. The potential activity of solid wastes such as waste ceramic powder, fly ash and slag is stimulated by an alkali activator to generate geopolymers to replace traditional ordinary cement as a binder, thereby improving the strength of lightweight aggregate concrete and maintaining its lightweight characteristics. The performance of lightweight aggregate concrete is further improved by adding mixed fibers and composite admixtures.

[0037] Therefore, compared with the prior art, the lightweight and high-strength geopolymer concrete prepared by the present invention has the following advantages:

[0038] (1) The lightweight and high-strength geopolymer concrete prepared by the present invention can have a compressive strength of more than 50 MPa after 28 days, meeting the strength requirements of prefabricated buildings such as bridges, high-rise buildings, and tunnel segments;

[0039] (2) The lightweight and high-strength geopolymer concrete prepared by the present invention can take into account both lightness and high strength. The raw materials used are all solid waste, which realizes the recycling of waste and reduces the preparation cost of concrete;

[0040] (3) The present invention does not require calcination to produce cement during the production process, which has little pollution to the environment. The preparation process is simple and has low energy consumption, which meets the requirements of environmental protection and sustainable development. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The raw materials, equipment, etc. used in the following embodiments can be purchased through conventional channels unless otherwise specified.

[0042] Example 1 A lightweight and high-strength geopolymer concrete suitable for prefabricated buildings

[0043] The lightweight high-strength geopolymer concrete comprises the following components and their weight proportions: 90 parts of waste ceramic powder, 90 parts of Class I fly ash, 270 parts of slag, 198 parts of 1M sodium silicate solution, 695 parts of medium sand, 540 parts of shale ceramsite, 4.5 parts of mixed fiber; 9 parts of composite admixture solution; wherein the mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:2; the composite admixture solution is formed by Subot -ⅠPolycarboxylic acid high performance water reducing agent, zinc sulfate and water are prepared in a mass ratio of 1:1:6.

[0044] The method for preparing the lightweight and high-strength geopolymer concrete comprises the following steps:

[0045] S1, 24 hours in advance, add sodium hydroxide and water in proportion to water glass with a raw material modulus of 2.39 to prepare a 1M sodium silicate solution to obtain an alkali activator for standby use;

[0046] S2, soaking the shale ceramsite in water for 2 hours, and then spreading it out to naturally air dry to a saturated surface dry state to obtain pre-soaked light coarse aggregate;

[0047] S3, Subote -ⅠPolycarboxylate high performance water reducing agent, zinc sulfate and water are diluted and mixed in a ratio of 1:1:6 to obtain a composite admixture solution;

[0048] S4, weighing the waste ceramic powder, grade I fly ash, slag and medium sand by weight, stirring at 48 rpm for 2 min until uniform, then adding them to the pre-soaked light coarse aggregate obtained in step S2, stirring again at 48 rpm for 2 min until uniform, to obtain a mixed system I; during the preparation process, ensure that the total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag;

[0049] S5. Add the alkali activator obtained in step S1 and the composite admixture solution obtained in step S3 to the mixed system I obtained in step S4 in sequence, stir at 48 rpm for 2 min until the mixture is uniformly mixed, add the mixed fiber thereto, and continue stirring at 48 rpm for 2 min to allow the slurry to fully wrap the fine aggregate, light coarse aggregate and fiber.

[0050] The prepared lightweight and high-strength geopolymer concrete suitable for prefabricated buildings is injected into a mold, placed in a curing box for curing, and its compressive strength and density grade are measured after 28 days.

[0051] Example 2 A lightweight and high-strength geopolymer concrete suitable for prefabricated buildings

[0052] The lightweight high-strength geopolymer concrete comprises the following components and their weight proportions: 180 parts of waste ceramic powder, 45 parts of Class I fly ash, 225 parts of slag, 207 parts of 2M sodium silicate solution, 695 parts of medium sand, 540 parts of shale ceramsite, 13.5 parts of mixed fiber; 27 parts of composite admixture solution; wherein the mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; the composite admixture solution is formed by Subot -ⅠPolycarboxylate high-performance water reducer, zinc sulfate and water are prepared in a mass ratio of 2:1:9;

[0053] The method for preparing the lightweight and high-strength geopolymer concrete comprises the following steps:

[0054] S1, 24 hours in advance, add sodium hydroxide and water in proportion to water glass with a raw material modulus of 2.39 to prepare a 2M sodium silicate solution to obtain an alkali activator for standby use;

[0055] S2. Soak the shale ceramsite in water for 1.5 hours, then spread it out and air dry it naturally to a saturated surface dry state to obtain pre-soaked light coarse aggregate;

[0056] S3, Subote -ⅠPolycarboxylate high performance water reducing agent, zinc sulfate and water are diluted and mixed in a ratio of 2:1:9 to obtain a composite admixture solution;

[0057] S4, weighing the waste ceramic powder, grade I fly ash, slag and medium sand by weight, stirring at 48 rpm for 2 min until uniform, then adding them to the pre-soaked light coarse aggregate obtained in step S2, stirring again at 48 rpm for 2 min until uniform, to obtain a mixed system I; during the preparation process, ensure that the total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag;

[0058] S5. Add the alkali activator obtained in step S1 and the composite admixture solution obtained in step S3 to the mixed system I obtained in step S4 in sequence, stir at 48 rpm for 2 min until the mixture is uniformly mixed, add the mixed fiber thereto, and continue stirring at 48 rpm for 2 min to allow the slurry to fully wrap the fine aggregate, light coarse aggregate and fiber.

[0059] The prepared lightweight and high-strength geopolymer concrete suitable for prefabricated buildings is injected into a mold, placed in a curing box for curing, and its compressive strength and density grade are measured after 28 days.

[0060] Example 3 A lightweight and high-strength geopolymer concrete suitable for prefabricated buildings

[0061] The lightweight high-strength geopolymer comprises the following components and their weight proportions: 90 parts of waste ceramic powder, 45 parts of fly ash, 315 parts of slag, 207 parts of 1.5M sodium silicate solution, 695 parts of medium sand, 540 parts of shale ceramsite, 9 parts of mixed fiber; 18 parts of composite admixture solution; wherein the mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; the composite admixture solution is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; -ⅠPolycarboxylate high performance water reducing agent, zinc sulfate and water are prepared in a mass ratio of 1:1:6;

[0062] The method for preparing the lightweight and high-strength geopolymer concrete comprises the following steps:

[0063] S1, 24 hours in advance, add sodium hydroxide and water in proportion to water glass with a raw material modulus of 2.39 to prepare a 1.5M sodium silicate solution to obtain an alkali activator for standby use;

[0064] S2. Soak the shale ceramsite in water for 1 hour, then spread it out and air dry it naturally to a saturated surface dry state to obtain pre-soaked light coarse aggregate;

[0065] S3, Subote -ⅠPolycarboxylate high performance water reducing agent, zinc sulfate and water are diluted and mixed in a ratio of 1:1:6 to obtain a composite admixture solution;

[0066] S4, weighing the waste ceramic powder, grade I fly ash, slag and medium sand by weight, stirring at 48 rpm for 2 min until uniform, then adding them to the pre-soaked light coarse aggregate obtained in step S2, stirring again at 48 rpm for 2 min until uniform, to obtain a mixed system I; during the preparation process, ensure that the total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag;

[0067] S5. Add the alkali activator obtained in step S1 and the composite admixture solution obtained in step S3 to the mixed system I obtained in step S4 in sequence, stir at 48 rpm for 2 min until the mixture is uniformly mixed, add the mixed fiber thereto, and continue stirring at 48 rpm for 2 min to allow the slurry to fully wrap the fine aggregate, light coarse aggregate and fiber.

[0068] The prepared lightweight and high-strength geopolymer concrete suitable for prefabricated buildings is injected into a mold, placed in a curing box for curing, and its compressive strength and density grade are measured after 28 days.

[0069] Example 4 A lightweight and high-strength geopolymer concrete suitable for prefabricated buildings

[0070] The lightweight high-strength geopolymer comprises the following components and their weight proportions: 90 parts of waste ceramic powder, 45 parts of Class I fly ash, 315 parts of slag, 207 parts of 1.5M sodium silicate solution, 643 parts of medium sand, 567 parts of shale ceramsite, 9 parts of mixed fiber; 18 parts of composite admixture solution; wherein the mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; the composite admixture solution is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; -ⅠPolycarboxylate high performance water reducing agent, zinc sulfate and water are prepared in a mass ratio of 1:1:6;

[0071] The preparation method of the lightweight and high-strength geopolymer concrete is similar to that of Example 3.

[0072] The prepared lightweight and high-strength geopolymer concrete suitable for prefabricated buildings is injected into a mold, placed in a curing box for curing, and its compressive strength and density grade are measured after 28 days.

[0073] Comparative Example 1 A cement-based lightweight aggregate concrete

[0074] The composition and preparation method of the cement-based lightweight aggregate concrete are similar to those of Example 3, except that the aluminosilicate material and the activator are replaced by 450 parts of ordinary Portland cement and 180 parts of water;

[0075] The difference from Example 3 is that in Comparative Example 1, ordinary Portland cement and water are reacted to replace the method of reacting aluminosilicate material and alkali activator to generate gel in the present invention.

[0076] Comparative Example 2 A lightweight and high-strength geopolymer concrete

[0077] The composition and preparation method of the lightweight high-strength geopolymer concrete are similar to those in Example 3;

[0078] The difference from Example 3 is that Comparative Example 2 does not include mixed fibers and composite admixture solution.

[0079] Comparative Example 3 A lightweight and high-strength geopolymer concrete

[0080] The composition and preparation method of the lightweight high-strength geopolymer concrete are similar to those in Example 3;

[0081] The difference from Example 3 is that in Comparative Example 3, the composite fiber is replaced by pure polyvinyl alcohol fiber.

[0082] Comparative Example 4 A lightweight and high-strength geopolymer concrete

[0083] The composition and preparation method of the lightweight high-strength geopolymer concrete are similar to those in Example 3;

[0084] The difference from Example 3 is that in Comparative Example 4, the composite fiber is replaced by pure basalt fiber.

[0085] Comparative Example 5 A lightweight and high-strength geopolymer concrete

[0086] The composition and preparation method of the lightweight high-strength geopolymer concrete are similar to those in Example 3;

[0087] The difference from Example 3 is that in Comparative Example 5, the Subot in the composite admixture solution is -Ⅰ Polycarboxylic acid high performance water reducer replaced by Subot -A naphthalene-based high efficiency water reducer.

[0088] Comparative Example 6 A lightweight and high-strength geopolymer concrete

[0089] The composition and preparation method of the lightweight high-strength geopolymer concrete are similar to those in Example 3;

[0090] The difference from Example 3 is that in Comparative Example 6, zinc sulfate in the composite admixture solution is replaced by citric acid.

[0091] Test case performance test

[0092] 1. Test samples: lightweight high-strength geopolymer concrete and cement-based lightweight aggregate concrete prepared in Examples 1-4 and Comparative Examples 1-6;

[0093] 2. Test method: Refer to the industry standard "Technical Standard for Application of Lightweight Aggregate Concrete" (JGJ / T12-2019) to determine the dry apparent density of the above samples to divide the density grade, and refer to the national standard "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T 50081-2019 to determine the compressive strength of the above samples.

[0094] 3. Test results: The specific test results are shown in Table 1.

[0095] Table 1 Compressive strength and density grade test results of different test samples

[0096]

[0097]

[0098] As can be seen from Table 1, the 28-day compressive strength of the lightweight high-strength geopolymer concrete prepared in Examples 1-3 of the present invention is all above 55 MPa, indicating that while keeping the basic concrete proportions such as total aluminosilicate material, fine aggregate, light coarse aggregate content and total water content unchanged, appropriately adjusting factors such as the proportion of aluminosilicate material, alkali activator modulus M, mixed fiber content, composite admixture content and light coarse aggregate pre-impregnation time will not have a significant effect on the compressive strength; Example 4 prepared with reference to the best example 3, by increasing the proportion of light coarse aggregate in the total aggregate, the concrete density grade is reduced to 1800 kg / m 3 , and the 28-day compressive strength remains above 50MPa.

[0099] Compared with the best embodiment 3, in comparative example 1, ordinary cement is used to generate gel, and the compressive strength of the concrete decreases by 18 MPa; in comparative example 2, due to the lack of addition of mixed fibers and composite admixture solution, the performance of the concrete also decreases significantly; in comparative examples 3 and 4, the two fibers are used alone, and a crack control system from micro to macro is not formed, and the compressive strength improvement effect is not as good as the synergistic effect of the mixed fibers; in comparative examples 5 and 6, due to the use of water reducers and retarders that are not suitable for geopolymer systems, the improvement effect of the composite admixture solution on the compressive strength is weakened.

[0100] Therefore, compared with traditional cement-based lightweight aggregate concrete, the lightweight high-strength geopolymer concrete of the present invention has higher compressive strength and can be used in prefabricated buildings such as bridges, high-rise buildings, and tunnel segments. In addition, the raw materials used in the present invention are all solid waste, with low cost and simple preparation process, which meets the requirements of environmental protection and sustainable development.

[0101] Finally, it should be noted that the above embodiments are only illustrative of the principles, performance and efficacy of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A lightweight and high-strength geopolymer concrete suitable for prefabricated buildings, characterized in that: The invention comprises the following components and their weight proportions: 90-180 parts of waste ceramic powder, 45-135 parts of fly ash, 225-315 parts of slag, 158-256 parts of alkali activator, 626-765 parts of fine aggregate, 504-576 parts of light coarse aggregate, 4.5-13.5 parts of mixed fiber; 1-36 parts of composite admixture solution; The alkaline activator is a 1-2M sodium silicate solution; The mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:1.5 to 3; The composite admixture solution is prepared from an organic water reducer, an inorganic retarder and water in a mass ratio of 1 to 3:1:6 to 12; The total amount of water in the alkali activator and the composite admixture solution is 40wt% of the total amount of the waste ceramic powder, fly ash and slag.

2. The lightweight high-strength geopolymer concrete according to claim 1, characterized in that: The invention comprises the following components and their weight proportions: 90 parts of waste ceramic powder, 45 parts of fly ash, 315 parts of slag, 207 parts of alkali activator, 695 parts of fine aggregate, 540 parts of light coarse aggregate, 9 parts of mixed fiber; 18 parts of composite admixture solution; The alkaline activator is a 1.5M sodium silicate solution; The mixed fiber is formed by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:3; The composite admixture solution is prepared from an organic water reducer, an inorganic retarder and water in a mass ratio of 1:1:

6.

3. The lightweight high-strength geopolymer concrete according to claim 1 or 2, characterized in that: The waste ceramic powder is prepared by crushing, washing, selecting and ball milling ceramic waste such as wall tiles, floor tiles, daily ceramics, etc., and the particle size is 325-800 meshes.

4. The lightweight high-strength geopolymer concrete according to claim 1 or 2, characterized in that: The fly ash is of grade I or II, and the total content of SiO2 and Al2O3 is not less than 80wt%; the slag is S95 grade blast furnace granulated slag powder.

5. The lightweight and high-strength geopolymer concrete according to claim 1 or 2, characterized in that: The preparation process of the alkali activator is as follows: 2.3-3.4M industrial water glass is used as a raw material, and sodium hydroxide and water are added to adjust the modulus M.

6. The lightweight and high-strength geopolymer concrete according to claim 1 or 2, characterized in that: The fine aggregate is medium sand; the light coarse aggregate is shale ceramsite with a particle size of 5 to 20 mm and a bulk density of 700 to 900 kg / m 3 .

7. The lightweight and high-strength geopolymer concrete according to claim 1 or 2, characterized in that: In the mixed fiber, the length of the polyvinyl alcohol fiber is 2-4 mm and the diameter is 14-16 μm; the length of the basalt fiber is 5-7 mm and the diameter is 16-18 μm.

8. The lightweight and high-strength geopolymer concrete according to claim 1 or 2, characterized in that: In the composite admixture solution, the organic water reducer is a polycarboxylic acid water reducer; and the inorganic retarder is zinc sulfate.

9. A method for preparing the lightweight and high-strength geopolymer concrete according to any one of claims 1 to 8, characterized in that: The steps include: S1, mixing water glass, sodium hydroxide and water to prepare an alkali activator of the required modulus for standby use; S2. Soak the light coarse aggregate in water for 1 to 2 hours, and then spread it out to dry naturally until it reaches a saturated surface dry state, thereby obtaining pre-soaked light coarse aggregate; S3, diluting and mixing the organic water reducing agent, the inorganic retarder and water in proportion to obtain a composite admixture solution; S4, weighing the waste ceramic powder, fly ash, slag and fine aggregate by weight, stirring them evenly, and then adding them to the pre-soaked light coarse aggregate obtained in step S2, stirring them evenly again, to obtain a mixed system I; S5. Add the alkali activator obtained in step S1 and the composite admixture solution obtained in step S3 to the mixed system I obtained in step S4 in sequence, stir evenly, add the mixed fiber thereto, and continue stirring so that the slurry fully wraps the fine aggregate, light coarse aggregate and fiber.

Citation Information

Patent Citations

  • Geopolymer-based foam concrete for roads and preparation method of geopolymer-based foam concrete

    CN113264719A

  • Lightweight high-durability concrete and preparation method thereof

    CN115974482A

  • High-performance geopolymer concrete and preparation method thereof

    CN113998929A

  • Geopolymer concrete taking waste ceramic powder as admixture and preparation of geopolymer concrete

    CN116903304A